The prevalence and etiological profile of short stature in children - Ali Mosa Sadiq; Qusay Farhan Hassan; Yaareb Abdulghafoor Mutlag (Genius Journals, 2022)
According to the survey, 97% of parents of young adolescents do not know that their shortness is caused by certain diseases and mistakenly believe that it is a delay in the development of the child or hereditary factors: only 1.6% of parents know that there is a possibility of disease; 41.9% of parents have medical knowledge; 32.3% do not believe that short stature is a disease and will grow taller in the future; 29% know short stature can be cured
Keywords: information; short; believe; medical